ALAT TULANG SITUS PLESTOSEN JAWA: BAHAN BAKU, TEKNOLOGI, DAN TIPOLOGI [Bone tools from Pleistocene Site of Java: Raw Materials, Technology, and Typology] - Abdullah, Ilham (Jurnal Penelitian Arkeologi Papua dan Papua Barat, 2015)
During this time knowledge about Homo erectus bones tool comes only from trusted Ngandong, but now it has a lot of bone tools found and published on the Site Pleistocene in Java. This paper is the result of a data-base processing using microscopic methods against all findings bone tools from sites Pleistocene in Java which aims to provide comprehensive information about the presence of bone tools. A total of 48 specimens of bone tools findings of Sangiran, Ngandong Site, Site Sambungmacan, Patiayam Site and Site Bringin. The analysis showed that there are 12 types of anatomical components of animal bones were used as tools. Type of animal bones were used as a bone tool is Cervus sp. (deer), Cervus hippelaphus (deer), Sus sp. (pig), Bos sp. (cow), Bibos palaeosondaicus (bull), rhinoceros (rhinoceros), Elephantidae (the elephants), and Bovidae. The technique used in making bone tools are broken techniques, pruning techniques, techniques sides, press techniques, and techniques rub. This type of tool is produced bone knife, lancipan, spatula, and spear AbstrakSelama ini pengetahuan tentang alat tulang Homo erectus hanya berasal dari Situs Ngandong, tetapi sekarang ini telah banyak alat tulang ditemukan dan dipublikasikan dari Situs Plestosen di Jawa. Tulisan ini merupakan hasil pengolahan data-base menggunakan metode mikroskopis terhadap semua temuan alat tulang dari situs-situs Plestosen di Jawa yang bertujuan memberi informasi komprehensif tentang keberadaan alat tulang. Sebanyak 48 spesimen alat tulang temuan dari Situs Sangiran, Situs Ngandong, Situs Sambungmacan, Situs Patiayam, dan Situs Bringin. Hasil analisis menunjukkan bahwa terdapat 12 jenis komponen anatomis binatang yang digunakan sebagai alat tulang. Jenis binatang yang tulangnya digunakan sebagai alat tulang adalah Cervus sp. (rusa), Cervus hippelaphus (rusa), Sus sp. (babi), Bos sp. (sapi), Bibos palaeosondaicus (banteng), rhinoceros (badak), elephantidae (gajah), dan bovidae. Teknik yang digunakan dalam membuat alat tulang adalah teknik pecah, teknik pangkas, teknik belah, teknik tekan, dan teknik gosok. Jenis alat tulang yang dihasilkan adalah pisau, lancipan, spatula dan mata tombak.